Inbreeding Depression and Purging in Fertility and Longevity Traits in Sheep Breeds from Germany - Cathrin Justinski; Jens Wilkens; Ottmar Distl (Animals)
In the present study, we analysed fertility and longevity traits of 22 sheep breeds from Germany with a suitable quantity of data in the national database OviCap. The data comprised merino, meat, country and milk sheep breeds with 62,198 ewes and about 173,000 lambing records, until the fifth lambing. Across-breed means of heritabilities reached estimates of 0.13, 0.17 and 0.18 for number of lambings, average number of lambs born per lambing and number of lambs per lifetime, respectively. For age at first lambing, length of lifetime and productive life, mean heritabilities over breeds were 0.34, 0.17 and 0.32, respectively. The across-breed means of the individual rate of inbreeding were significantly negative for the average number of lambs born per lambing and number of lambs born per lifetime, and for number of lambings it was close to the significance threshold. We found declining slopes for inbreeding depression for the average number of lambs born per lambing and number of lambs born per lifetime in 16 breeds, and significantly negative slopes in five and seven breeds. For lifetime and productive life, 9/22 and 8/22 breeds showed significant inbreeding depression, while for age at first lambing, only 1/22 breeds showed significant inbreeding depression. A significant reduction in inbreeding depression due to purging effects was found for eight breeds. Fitness traits may be subject to forced directional selection. Therefore, sheep breeding programmes should give special consideration to fertility and longevity traits. Fitness related traits seem to be essential in conservation of genetic diversity within sheep breeds.